The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1365-2745.13097
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood diversity simultaneously increased and decreased susceptibility to contrasting herbivores in an early stage forest diversity experiment

Abstract: 1. Forest structure and diversity can regulate tree vulnerability to damage by insects and pathogens. Past work suggests that trees with diverse neighbours should experience less leaf herbivory and less damage from specialist herbivores and diseases, and that the effect of neighbourhood diversity should be strongest at small spatial scales.2. In an early stage temperate tree diversity experiment, we monitored damage from leaf removing herbivores, specialist (gallers and leaf miners) herbivores, and two special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 96 publications
(142 reference statements)
2
27
1
Order By: Relevance
“…This supports former evidence suggesting that foliar fungal pathogens have the potential to maintain competitive differences between tree species (Spear & Mordecai, 2018) and can be regulated by the diversity of the surrounding tree community (Grossman et al, 2019).…”
Section: Resultssupporting
confidence: 90%
“…This supports former evidence suggesting that foliar fungal pathogens have the potential to maintain competitive differences between tree species (Spear & Mordecai, 2018) and can be regulated by the diversity of the surrounding tree community (Grossman et al, 2019).…”
Section: Resultssupporting
confidence: 90%
“…First, it may reflect increasing complementarity effects dependent on the dispersion of functional traits not correlated with shade tolerance dissimilarity (Paquette et al ). Second, higher phylogenetic dissimilarity may buffer trees against the negative effects of specialist pest and pathogen outbreaks (Parker et al ; Grossman et al ). Studies have suggested that outbreaks of pests such as spruce budworm have increased in intensity in our study region (Boucher et al ) and regions previously inaccessible to the pest due to cold temperatures will become more susceptible as the climate warms (Pureswaran et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phylogenetic dissimilarity may affect tree growth through a reduction in susceptibility to species–specific pests, pathogens and/or predators. Originally developed to describe patterns of seedling recruitment (Janzen ; Connell ), this theory has been extended to mature plants in the form of the resource concentration hypothesis (Parker et al ; Grossman et al ). The theory stipulates that mature plant communities with high abundances of phylogenetically close host species are more susceptible to specialised pest and pathogen outbreak than those with higher phylogenetic dissimilarity.…”
Section: Introductionmentioning
confidence: 99%
“…Here, for reference, we include stand-replacing fire, a common disturbance type of stand-replacing disturbances in North America as an example. Previous studies have revealed that resource conditions are liable to be affected by stand-replacing fire disturbances [8,12,[33][34][35], which result in increased light, soil nutrients, pH, and soil temperatures, and a decrease in the organic layer depth [15]. Immediately after fire, adequate growth space and resource availability greatly favor the establishment of vascular plants, which are fast-growing, nutrient-demanding, and shade-intolerant [8].…”
Section: Colonization Timementioning
confidence: 99%